2017
DOI: 10.1080/13825585.2017.1319144
|View full text |Cite
|
Sign up to set email alerts
|

Age, criterion flexibility, and item recognition

Abstract: We examined young and older adults' ability to flexibly adapt response criterion on a recognition test when the probability that a test item had been studied was cued by test color. One word color signaled that the probability of the test item being old was 70% and a second color signaled that the probability of the test item being new was 70%. Young and older adults demonstrated similar levels of criterion shifting in response to color cues. Moreover, although both young and older adults were slowed when test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Both young and older adults had more liberal criteria when instructed to base recognition on category membership rather than on specific items, but young adults showed a somewhat greater shift than did older adults. On the other hand, neither Konkel et al (2015) nor North et al (2017) observed age differences in ability to shift criterion when the likelihood that test items were old or new was cued on each trial. Konkel et al (2015) reported that older adults were slowed more than young adults when cues were invalid, but North et al (2017) did not replicate this finding.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Both young and older adults had more liberal criteria when instructed to base recognition on category membership rather than on specific items, but young adults showed a somewhat greater shift than did older adults. On the other hand, neither Konkel et al (2015) nor North et al (2017) observed age differences in ability to shift criterion when the likelihood that test items were old or new was cued on each trial. Konkel et al (2015) reported that older adults were slowed more than young adults when cues were invalid, but North et al (2017) did not replicate this finding.…”
Section: Discussionmentioning
confidence: 83%
“…The fact that young and older adults did not differ in general response bias in the present study, then, might be attributable to the fact that levels of discrimination of old from new test items were similar across age, leaving open the possibility that age differences in criterion placement might manifest under conditions in which larger age differences in discrimination are observed. The extant literature, however, suggests a variable relationship between age differences in sensitivity and age differences in response criterion across studies (e.g., Aizpurua & Koutstaal, 2010; Cassidy & Gutchess, 2016; Criss et al, 2014; Konkel et al, 2015; Marquie & Baracat, 2000; North et al, 2017; Pendergrass et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have identified experimental manipulations that can reliably and robustly induce subjects to adopt a different criterion without affecting their discrimination ability, including revealing the base rate of old items, creating uneven monetary payoffs and penalties for “old” versus “new” responses, or simply warning subjects to avoid either misses (incorrect “new” judgments) or false alarms (incorrect “old” judgments; see Hockley, 2011, for a review). Recent research has examined various properties of criterion shifting, including the amount of effort that may be necessary to adapt a criterion (North, Olfman, Caldera, Munoz, & Light, 2018; Starns & Olchowski, 2015).…”
Section: Strategically Adapting a Criterion To Suit The Situationmentioning
confidence: 99%
“…Conversely, older adults may be less flexible in adjusting decision criteria and always used a 'respond to auditory' strategy. However, studies reporting age-related differences on temporal multisensory tasks (McGovern et al, 2014;Setti et al, 2013) and item-recognition tasks (North et al, 2018) reveal similar response criteria but different perceptual sensitivities between young and old adults. While it is likely that reduced precision in detecting asynchronies is a strong driver of the current results, flexibility in updating response criterion could be task-dependent and a contributing factor.…”
Section: Expansion and Compression Effects On Visual Duration Perceptmentioning
confidence: 97%